The Influence of Digital Talent and Career Development Support on Retention Intention: The Mediating Roles of Career Adaptability and Employee Engagement among Teachers at SMK Korpri Majalengka Regency - Muhamad Rifai; Anna Wulandari; Muhamad Ekhsan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Digital transformation in the vocational education sector requires educators to have adequate digital competencies to be able to adapt to the development of learning technology. This study aims to analyze the influence of Digital Talent and Career Development Support on Retention Intention mediated by Career Adaptability and Employee Engagement in teachers of SMK Korpri Majalengka Regency. This study uses a quantitative approach with a survey method. Data was obtained through the distribution of questionnaires to teachers of SMK Korpri Majalengka Regency and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS). The results of the study show that Digital Talent and Career Development Support have an important role in increasing teachers' Retention Intention. In addition, Career Adaptability and Employee Engagement function as mediating variables that strengthen the relationship between Digital Talent and Career Development Support to Retention Intention. The findings of this study imply that improving digital competence, career development support, career adaptability, and work attachment need to be the main focus in human resource management strategies in vocational education institutions to maintain quality educators.